2015
DOI: 10.5296/jee.v6i1.7442
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corporate Governance on the Extent of Corporate Social Responsibility and Environmental Reporting

Abstract: This study examines the influence of corporate governance on the extent of corporate social responsibility and environmental reporting (CSER) in Libyan companies according to legitimacy theory, using quantitative and qualitative methods. The variables used in this study are government ownership, chief executive officer duality, board independence, and board size. The study was conducted in Libya because this country has a unique political and economic system. Moreover, the regime in Libya has influenced the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Hanniffa and Cook [14], Nurhayati et al [130], Walls et al [18] and Ortiz-de-Mandojana et al [130] all found that the presence of non-executive and independent directors on company boards has a negative influence on CSP. In addition, Rodríguez-Ariza et al [135], Benomran et al [85] and Walls et al [19,144] found no significant association between board independence and CSP.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…Hanniffa and Cook [14], Nurhayati et al [130], Walls et al [18] and Ortiz-de-Mandojana et al [130] all found that the presence of non-executive and independent directors on company boards has a negative influence on CSP. In addition, Rodríguez-Ariza et al [135], Benomran et al [85] and Walls et al [19,144] found no significant association between board independence and CSP.…”
Section: Linking Board Independence and Corporate Social Performancementioning
confidence: 99%
“…Further and notwithstanding the lack of evidence relating to the governance-CSRD nexus, to the best of our knowledge, there is only one research that has examined whether governance structure can affect CSRD. Benomran et al (2015) examined the effect of corporate governance on the CSR and environmental reporting levels in Libyan companies using mixed methods. However, the paper is somewhat limited.…”
Section: Introductionmentioning
confidence: 99%
“…First, the sample of Benomran et al (2015) contains financial (38 per cent) and non-financial firms, which may mislead the quantitative results due to the nature of financial firms. Second, although Benomran et al (2015) partially examined the oil sector, their sample is limited; their sample only contains 12 companies (45 per cent of total observations). We have extended the sample to include all oil and gas firms with a total of 112 observations in a relatively more recent period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, having many persons sit on the board with various experience and qualifications may enhance their legitimacy. Past studies have demonstrated a strong association between sustainability or environmental practices and board size [31,[52][53][54]. Benomran, et al [52], who studied the effect of board size on corporate social and environmental disclosure in Libya, revealed the positive and significant linkage between the two.…”
Section: Hypothesis 2 (H2mentioning
confidence: 97%